Artificial Intelligence in Design and Impact on Electronic Marketing in Companies - Alqudah, Ali Mohammad Ali; Jaradat, Yousef M.; AlObaydi, Basim Abbas Ali; Alqudah, Derar; Al Qudah, Emran (Mohamad Ali) Abdalah; Jarah, Baker Akram Falah (Journal of Ecohumanism, 2024)
E-marketing refers to the use of technology and artificial intelligence to analyze and interpret marketing data. In addition to providing recommendations and guidance to improve marketing campaigns, improve user experience, and increase sales. These tools include data analytics, machine learning, data classification and aggregation, voice and image recognition, and natural language. Therefore, this study aimed to identify the effect of artificial intelligence (AI) in Design on E-Marketing in Companies. This study used a survey design with a quantitative approach, with the target group being workers of E-Marketing companies. A 198 surveys were also gathered from Jordanian E-Marketing companies, however, 187 questionnaires were judged viable for study. Where the results indicate AI positively affects E-Marketing, and natural language processing, analytical models, content marketing, and digital marketing affect E-Marketing.